The role of temperature and the NAO index in the changing snow-related variables in European regions in the period 1900‒2010 - Kis, Anna; Pongrácz, Rita (Hungarian Geographical Bulletin, 2021)
Snow-related variables are analysed in the present paper in the period 1901‒2010 on the basis of the ERA-20C dataset. Relationships between different snow characteristics, temperature and the NAO index are investigated on monthly, yearly and decadal scales for eight regions within Europe representing different climatic types (i.e. oceanic, continental, polar) to analyse the differences and similarities between them depending on the climatic conditions. According to our results, the ratio of snow (i.e. snowfall compared to total precipitation) can reach 1 in winter in the colder, northern regions, whereas it is about 0.6 in the continental areas of Central Europe, even in the coldest months. During a strong positive phase of NAO more snow falls in the northern regions of Europe due to the large-scale circulation characteristics. When a negative NAO phase occurs, the temperature and snowfall anomalies are the opposite in northern Europe. The highest temperature values generally occurred after 2000, and the snowfall amount was smaller in the first decades of the 21st century compared to the previous decades. The relationship between temperature and snowfall is the strongest in autumn in the colder regions; in spring in the continental areas and in winter in the oceanic climate.